Single Dose of Tolvaptan In The Management of Intracranial Haemorrhage Induced Syndrome of Inappropriate Antidiuretic Hormone- A Case Report - Keyal, Niraj Kumar; Shah, Pramanand; Sah, Manbodh Kumar; Mahato, Ramesh (Med Phoenix, 2023)
Hyponatraemia is a common manifestation of a syndrome of inappropriate antidiuretic hormone secretion in neurological patients admitted to the intensive care unit. We present a case of 62-years old male who presented with loss of consciousness, seizure, and altered mental status and was diagnosed to have right-sided intracranial haemorrhage. The patient underwent evacuation of hematoma and developed persistent hyponatremia secondary to the syndrome of inappropriate antidiuretic hormone. Patient was treated with 3%sodium chloride, loop diuretics, and fluid restriction. There was no improvement in hyponatremia after initial correction and we started on 7.5 milligrams of Tolvaptan. The patient responded within 4 days of starting Tolvaptan. There was no hyponatraemic episode during the follow-up. From this, we want to emphasize that refractory hyponatremia secondary to intracranial haemorrhage should be treated with Tolvaptan.